Clinicoradiological Outcomes of Surgical Revascularization for Moyamoya Disease with minimum 10-year follow-up. (16th November 2020) - Li, Yiping; Wang, Allan; Steinberg, Gary K
Abstract: INTRODUCTION: The long-term progression of disease and recurrence rate of symptomatic events after surgical revascularization for moyamoya disease (MMD) are unknown. METHODS: Patients with MMD operated on between 1991 and 2009 were prospectively enrolled into the departmental database. RESULTS: 230 revascularization (87% combined direct and indirect and 13% indirect alone) procedures were performed on 129 patients for the treatment of MMD with a long-term bypass patency rate of 98%. Unilateral presentation was identified in 39 (30.2%) compared to 90 (69.8%) with bilateral MMD. Posterior circulation (PC) involvement was identified in 34 (26.4%) patients. Over a median follow-up period of 13 years (range 10–26 years), 15 (38.5%) patients experienced radiographic progression of unilateral disease and 14 (10.9%) experienced PC radiographic progression. Delayed surgical revascularization of the untreated contralateral anterior circulation was performed on 11 (28.2%) patients due to symptomatic progression of disease. Progression of PC disease occurred only in patients with PC involvement upon presentation. No patient underwent PC revascularization for symptomatic progression. Aside from those with unilateral progression, fourteen additional patients (10.9%) experienced delayed cerebrovascular accidents (CVAs) 8 of which were ischemic and 6 were hemorrhagic strokes. None of the CVAs were located within the posterior circulation. Twelve delayed CVAs occurred in a previously revascularized hemisphere while one occurred in an un-diseased hemisphere from a micro pseudoaneurysm. Repeat revascularization was performed in 6 patients while 4 were managed conservatively and 4 were deceased. Relative to baseline presenting mRS, 92.2% of patients were improved or unchanged at 10 year follow-up. On multivariate regression, progression of the PC predicted the development of delayed CVA (Odds ratio 8.1, 95% CI 1.1-59.2) while pre-operative stroke (Odds ratio 3.4, 95% CI 1.2-9.8) presentation and progression of disease was predictive of 10-year outcome (Odds ratio 4.0, 95% CI 1.5-10.6). CONCLUSION: Good functional outcomes over a median follow-up period of 13 years support the strategy of revascularization for MMD patients. Disease progression of the posterior circulation is common and may reduce pial-pial collaterals resulting in delayed CVAs.